PENERAPAN HUKUM PROGRESIF UNTUK PENEGAKKAN HUKUM DI DALAM PUTUSAN HAKIM YANG BERKEADILAN - Mansur, Mansur; Atoillah, Atoillah; Yamin, Saefullah (Universitas Wiralodra, 2024)
Indonesian judicial practice where justice is often measured based on the application of laws and regulations on-sich so that judges in deciding cases as they are in the law, then the decision is considered a fair decision. Many things happen in the judicial process in our country where it is not uncommon for law enforcers to be trapped in laws and regulations that are free from values, so that injustice arises and finally makes the people miserable. The purpose of this study is to explain why judges' decisions are influential in an effort to provide fair law enforcement, as well as to explain the need for the application of progressive law in law enforcement. The method used in this scientific dissertation uses two approaches, including the socio-legal approach, which is qualitative, based on literature data, and the normative juridical approach is used to analyze the norms of laws and regulations. Judges must indeed decide based on the law, but in fact they do not only spell out the text of the law, but decide what is stored in the text, the philosophy behind progressive law is not law for law, but law for man. So that the judge's decision is not necessarily only a decision that is ready to be displayed in the text, but the values contained in the decision must provide a sense of justice.